Potential role of chromatin remodeling factor genes in atrophic gastritis/gastric cancer risk - Bilgiç, Fahri; Gerçeker, Emre; Örenay Boyacıoğlu, Seda; Kasap, Elmas; Demirci, Ufuk; Yıldırım, Hatice; Baykan, Ahmed Ramiz; Yüceyar, Hakan (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Atrophic gastritis (AG), intestinal metaplasia (IM), and Helicobacter pylori (HP) are the risk factors for the development of gastric cancer (GC). Chromatin remodeling is one of the epigenetic mechanisms involved in the carcinogenesis of GC. The purpose of this study was to investigate the expression profiles of defined chromatin remodeling genes in gastric mucosal samples and their values as gastric carcinogenesis biomarkers. Materials and Methods: In total, 95 patients were included in the study. Patients were divided into 3 groups as: GC group (n=34), AG group (n=36), and control group (n=25). AG group was further divided into subgroups based on the presence of HP and IM in gastric mucosa. Chromatin remodeling gene expressions were analyzed using real-time PCR (RT-PCR) array in all groups. Data were evaluated using the RT-qPCR primer assay data analysis software. Results: EED, CBX3, and MTA1 were more overexpressed, whereas ARID1A, ING5, and CBX7 were more underexpressed in the AG and GC groups compared with the controls. No significant differences were observed between the AG and GC groups concerning the expression of these 6 genes, although the fold change levels of these genes in the GC group were well above than in the AG group. EED, CBX3, and MTA1 were significantly more overexpressed in HP- and IM-positive AG subgroup compared with the HP- or IM-negative AG subgroup. Conclusion: In conclusion, our results provide an evidence of epigenetic alterations in AG. Expressions of EED, CBX3, MTA1, ARID1A, ING5, and CBX7 may be considered as promising markers to be used in GC screening for patients with AG. Cite this article as: Bilgiç F, Gerçeker E, Örenay Boyacıoğlu S, et al. Potential role of chromatin remodeling factor genes in atrophic gastritis/gastric cancer risk. Turk J Gastroenterol 2018; 29: 427-35.